Silicon in prevention of atherosclerosis and other age-related diseases - Dudek, Łukasz; Kochman, Wacław; Dziedzic, Ewelina (Frontiers in Cardiovascular Medicine, 2024)
Researchers' interest in silicon as an element important for the functioning of the animal and human body began in the 1970s. Soluble compounds of silicon bioavailable from water and food seem to have important meaning for life processes occurring in the body. So far, researchers have focused on the significance of silicon for the development of bones and connective tissue, and its role in preventing neurodegenerative diseases and atherosclerosis. Despite numerous studies, the role of silicon as an active element in the human body is poorly understood. Since the involvement of lipid oxidation and inflammatory processes in the pathogenesis of atherosclerosis is well known, this article summarizes and discusses the current research and scientific observations regarding silicon, primarily in terms of its beneficial influence on redox and anti-inflammatory reactions and the lipid profile. The association of silicon with the stabilization of the structure of glycosaminoglycans and their protein complexes may also support the anti-atherosclerotic effect. The authors attempted to collect and present existing publications that could confirm the beneficial role of dietary silicon in the prevention of age-related diseases and explain the potential mechanisms of its action.